1966
DOI: 10.1039/tf9666200759
|View full text |Cite
|
Sign up to set email alerts
|

Stability of hydrophobic sols in the presence of non-ionic surface-active agents. Part 2.—Stability of silver iodide sols in the presence of non-ionic surface-active agents

Abstract: The flocculation of positively-and negatively-charged silver iodide sols by divalent and trivalent ions has been examined in the presence of a series of alkyl polyoxyethylene glycol monoethers. As the concentration of non-ionic detergent was increased the concentration of inorganic salt required to produce flocculation also increased. The increase in stability of the sols produced by the adsorption of the non-ionic detergents could partly be accounted for by the reduction of the attractive forces between the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1966
1966
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The same type of For u values from 0.01 to about 0.5, the adsorption isoprofile has been observed in a series of polydispersed surfactherm is part of a sigmoidal curve. It implies a cooperative tants of the Triton X series adsorbed on silica (8), and process concerning mostly the polar moieties parallel to the polyoxyethylene oxides adsorbed on silver iodide crystals surface and the alkyl chains perpendicular to that surface (30). However in the former case, the hydrocarbon chain (23).…”
Section: Figmentioning
confidence: 98%
“…The same type of For u values from 0.01 to about 0.5, the adsorption isoprofile has been observed in a series of polydispersed surfactherm is part of a sigmoidal curve. It implies a cooperative tants of the Triton X series adsorbed on silica (8), and process concerning mostly the polar moieties parallel to the polyoxyethylene oxides adsorbed on silver iodide crystals surface and the alkyl chains perpendicular to that surface (30). However in the former case, the hydrocarbon chain (23).…”
Section: Figmentioning
confidence: 98%
“…Behrens and Borkovec [8] speculated that there is an additional stabilization mechanism through steric repulsion in the system studied by Liang and Morgan. It is shown that the steric repulsion by non-ionic surfactants works as a stabilization mechanism at the minimum stability ratio from the fact that the fastest rate is slower than the fastest rate induced by salt [8,38]. The hydrophilic part of non-ionic surfactants may not be strongly attracted to the solid-water interface, but may be extended to the water phase.…”
Section: Stability Ratio Of Hematite In the Presence Of Anionic Surfamentioning
confidence: 99%
“…ref. (28)). Assuming A to be independent of T, this value is substituted in the flocculation equation at 25"; from the measured flocculation concentration od is found and subtraction gives then om+.…”
Section: Specific Adsorption Potential At 25°cmentioning
confidence: 99%